Left ventricular diverticulum presenting as a pulsating umbilical mass - Buys, D.G.; Brown, S.C.; Long, M. (SA Heart Journal, 2017)
A six-week old girl presented at Paediatric Cardiology after a pulsatile umbilical mass was noticed during routine post-natal visit. The baby was asymptomatic with no feeding difficulties and no history of cardiac failure.